Nonverbal communication and translation : new perspectives and challenges in literature, interpretation and the media - Poyatos, Fernando (Benjamins translation library, 1997)
This is the first book, within the interdisciplinary field of Nonverbal Communication Studies, dealing with the specific tasks and problems involved in the translation of literary works as well as film and television texts, and in the live experience of simultaneous and consecutive interpretation. The theoretical and methodological ideas and models it contains should merit the interest not only of students of literature, professional translators and translatologists, interpreters, and those engaged in film and television dubbing, but also to literary readers, film and theatergoers, linguists a.